2014
DOI: 10.3109/09687637.2013.870534
|View full text |Cite
|
Sign up to set email alerts
|

Key challenges in providing services to people who use drugs: The perspectives of people working in emergency departments and shelters in Atlantic Canada

Abstract: AimsMany people who use drugs (PWUD) have multiple health and social needs, and research suggests that this population is increasingly accessing emergency departments (EDs) and shelters for health care and housing. This qualitative study explored the practices of those working in EDs and shelters when providing services to PWUD, with a particular focus on key challenges in service provision.MethodsEDs and shelters were conceptualized as ‘micro environments’ with various components (i.e. social, physical and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(51 reference statements)
0
8
1
Order By: Relevance
“…26,27,29 Our finding that physicians valued addictions-trained ancillary staff and locally developed pathways is consistent with the findings of other North American studies. [25][26][27]29 Although our study physicians' self-efficacy score in treating PWUD was higher than previously reported elsewhere, 3 the low proportion of physicians scoring highly is discouraging and may reflect the lack of PWUD treatment resources identified by some of our ED groups, frustration with ED care of PWUD, 40 lower clinical regard for PWUD than for people with other conditions 41 and persistent stigma toward people with OUD and OUD-related medications. 20 Time constraints in the ED may be alleviated by easy-touse, locally appropriate clinical pathways and the availability Research of ED-based specialized staff to help with ED BUP.…”
Section: Discussioncontrasting
confidence: 60%
“…26,27,29 Our finding that physicians valued addictions-trained ancillary staff and locally developed pathways is consistent with the findings of other North American studies. [25][26][27]29 Although our study physicians' self-efficacy score in treating PWUD was higher than previously reported elsewhere, 3 the low proportion of physicians scoring highly is discouraging and may reflect the lack of PWUD treatment resources identified by some of our ED groups, frustration with ED care of PWUD, 40 lower clinical regard for PWUD than for people with other conditions 41 and persistent stigma toward people with OUD and OUD-related medications. 20 Time constraints in the ED may be alleviated by easy-touse, locally appropriate clinical pathways and the availability Research of ED-based specialized staff to help with ED BUP.…”
Section: Discussioncontrasting
confidence: 60%
“…To our knowledge, this is the first systematic review on harm reduction approaches and pharmacological interventions for this population. While our review did not focus exclusively on studies among populations experiencing homelessness, people experiencing homelessness and people who use substances both face considerable social marginalization, multiple physical and/or mental health concerns, and high rates of premature morbidity [79]. Our review found that these interventions reduce harms associated with substance use and mitigate morbidity and mortality [41,44,45,50,51,53,57,58,60,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Those not sampled in this study were people with chronic HCV infection, and potentially people who are less likely to attend tertiary clinics or hospitals where participants in these studies were recruited. People who may be less likely to attend such settings are marginalized people or those not engaged in the healthcare system, particularly PWID . This highlights the need to provide HCV testing and treatment in non‐tertiary clinics and other places where the people who need to access these services are most likely to visit.…”
Section: Discussionmentioning
confidence: 99%